Quality of Employee Performance at the Makassar City Ujung Tanah Sub-District Office - Suprianto Suprianto; Sitti Hardiyanti Arhas (Universitas Negeri Makassar, 2022)
The quality of employee performance is a community right that must be fulfilled by the government. This research is a qualitative descriptive study that aims to determine the quality of employee performance at the Ujung Tanah Sub-district Office of Makassar City. The types and sources of data used are Primary Data and Secondary Data. Data collection techniques used are Observation, Interview, Documentation. The research informants were 7 people, consisting of 1 person from the Head of Ujung Tanah Subdistrict, 3 people from the Employee Staff, and 3 people from the Community. Researchers act as the main instrument in collecting the necessary data and information. The data analysis technique used is Data Condensation, Data Display, Conclusion. The results showed that the performance of the Ujung Tanah Sub-District Office employees was as expected, however, there were still some aspects that needed to be improved. Judging from the indicators used by researchers in measuring the Quality of Employee Performance in terms of Productivity aspects, the category is quite good, Service Quality is in the good category, the efficiency is in the good category, the effectiveness is in the good category, the responsiveness in the category is quite good, and the responsibility is in the good category.